Digital Transformation and Perceived Audit Quality: The Roles of Professional Judgment and Skepticism among External Auditors in Turkmenistan - Myrat Durdyyev; Rahman Yusuvop (Journal of Business Innovation and Accounting Research, 2026)
Digital technologies are reshaping external audit procedures, but their relationship with audit quality depends on how auditors interpret technology-generated evidence and sustain professional skepticism. This study examines the associations among digital transformation, perceived audit quality, professional judgment, and professional skepticism in Turkmenistan, an under-researched Central Asian setting. A quantitative-dominant mixed-methods design combined survey responses from 187 accounting and audit professionals with semi-structured interviews involving 24 purposively selected participants. The survey model was estimated using partial least squares structural equation modeling with 5,000 bootstrap resamples, while interview transcripts were analyzed thematically. Digital transformation was positively associated with perceived audit quality (β = 0.412, p < 0.001), professional judgment (β = 0.367, p < 0.001), and professional skepticism (β = 0.298, p < 0.001). Professional skepticism and professional judgment were also positively associated with perceived audit quality. Indirect-effect tests indicated partial mediation through professional skepticism (β = 0.102, p < 0.001), professional judgment (β = 0.105, p < 0.001), and a serial pathway from professional skepticism to professional judgment (β = 0.036, p = 0.008). Interview evidence converged with the quantitative results by showing that analytics and automation improved coverage and efficiency while shifting, rather than replacing, human judgment. The findings suggest that technology investment is most likely to improve perceived audit quality when it is accompanied by training, data-governance controls, and institutional support for skeptical inquiry. Because the study is cross-sectional and relies primarily on self-reported perceptions, the results should not be interpreted as causal evidence of objectively measured audit quality